New and little-known Canadian Lasioglossum (Dialictus) (Hymenoptera: Halictidae) and an emended key to species. Issue 1 (10th November 2022) - Gardner, Joel; Gibbs, Jason
Abstract: A revised key to the 94 species of Lasioglossum ( Dialictus ) currently known to occur in Canada is presented, incorporating new species and taxonomic updates since the publication of the first key in 2010. Two new species, Lasioglossum ( Dialictus ) immigrans and Lasioglossum ( Dialictus ) onuferkoi, are described from Canada. Lasioglossum ( D .) ascheri, L. ( D .) stictaspis, and L . ( D .) tegulariforme are reported or confirmed from Canada for the first time. Lasioglossum ( D .) gaudiale (Sandhouse, 1924) and L . ( D .) helianthi (Cockerell, 1916) are resurrected from synonymy with L . ( D .) tegulariforme (Crawford, 1907). The following five new synonymies are established: L . ( D .) stictaspis (Sandhouse, 1923) (= L . ( D .) albuquerquense (Michener, 1937)); L. ( D .) ascheri Gibbs, 2011 (= L. ( D .) curculum Gibbs, 2011); L . ( D .) helianthi (Cockerell, 1916) (= L . ( D .) imbrex Gibbs, 2010); L . ( D .) megastictum (Cockerell, 1937) (= L . ( D .) punctiferellum (Cockerell, 1937)); and L . ( D .) obnubilum (Sandhouse, 1924) (= L . ( D .) lilliputense Gibbs, 2010). Previously undescribed males of L . ( D .) helianthi, L . ( D .) reasbeckae, L . ( D .) tegulariforme, and L . ( D .) weemsi are diagnosed and figured.